BEAST begins: sample characteristics and survey performance of the B-star Exoplanet Abundance Study - Janson, Markus; Squicciarini, Vito; Delorme, Philippe; Gratton, Raffaele; Bonnefoy, Mickaël; Reffert, Sabine; Mamajek, Eric E.; Eriksson, Simon C.; Vigan, Arthur; Langlois, Maud; Engler, Natalia; Chauvin, Gaël; et al. (Astronomy and astrophysics, 2021)
While the occurrence rate of wide giant planets appears to increase with stellar mass at least up through the A-type regime, B-type stars have not been systematically studied in large-scale surveys so far. It therefore remains unclear up to what stellar mass this occurrence trend continues. The B-star Exoplanet Abundance Study (BEAST) is a direct imaging survey with the extreme adaptive optics instrument SPHERE, targeting 85 B-type stars in the young Scorpius-Centaurus (Sco-Cen) region with the aim to detect giant planets at wide separations and constrain their occurrence rate and physical properties. The statistical outcome of the survey will help determine if and where an upper stellar mass limit for planet formation occurs. In this work, we describe the selection and characterization of the BEAST target sample. Particular emphasis is placed on the age of each system, which is a central parameter in interpreting direct imaging observations. We implement a novel scheme for age dating based on kinematic sub-structures within Sco-Cen, which complements and expands upon previous age determinations in the literature. We also present initial results from the first epoch observations, including the detections of ten stellar companions, of which six were previously unknown. All planetary candidates in the survey will need follow up in second epoch observations, which are part of the allocated observational programme and will be executed in the near future.
Gesehen am 09.07.2021